Ubiquitin regulates TORC1 in yeast Saccharomyces cerevisiae. Issue 2 (10th March 2016) - Hu, Kejin; Guo, Shuguang; Yan, Gonghong; Yuan, Wenjie; Zheng, Yin; Jiang, Yu
Summary: In the yeast Saccharomyces cerevisiae the TOR complex 1 (TORC1) controls many growth‐related cellular processes and is essential for cell growth and proliferation. Macrolide antibiotic rapamycin, in complex with a cytosol protein named FKBP12, specifically inhibits TORC1, causing growth arrest. The FKBP12‐rapamycin complex interferes with TORC1 function by binding to the FRB domain of the TOR proteins. In an attempt to understand the role of the FRB domain in TOR function, we identified a single point mutation (Tor2 W2041R ) in the FRB domain of Tor2 that renders yeast cells rapamycin resistant and temperature sensitive. At the permissive temperature, the Tor2 mutant protein is partially defective for binding with Kog1 and TORC1 is impaired for membrane association. At the restrictive temperature, Kog1 but not the Tor2 mutant protein, is rapidly degraded. Overexpression of ubiquitin stabilizes Kog1 and suppresses the growth defect associated with the tor2 mutant at the nonpremissive temperature. We find that ubiquitin binds non‐covalently to Kog1, prevents Kog1 from degradation and stabilizes TORC1. Our data reveal a unique role for ubiquitin in regulation of TORC1 and suggest that Kog1 requires association with the Tor proteins for stabilization. Abstract : Under stress condition TORC1 is stabilized by binding with ubiquitin through Kog1 (A). Defects in the association with the Tor proteins cause Kog1 degradation under stress condition (B).